Literature review: the Effect of Company Size, Company Growth, and Company Liquidity on Going Concern Audit Opinion - Winarta, Wiwiek; Kuntadi, Cris (Dinasti Publisher, 2022)
Factors affecting going concern audit opinions have always been the focus of academic research. This article categorizes relevant previous research in Indonesia and analyzes several variables affecting audit opinion. This article examines the relationship or effect of company size, company growth, and company liquidity on going concern audit opinions, a study of auditing literature. This article aims to build a hypothesis of the effect between variables to be used in further research. This literature study shows the following results: 1) Company size has a negative effect on going concern audit opinion; 2) Company growth has a negative effect on going concern audit opinion; 3) Company liquidity has a negative effect on going concern audit opinion. This article provides a reference for more in-depth research on the factors affecting going concern audit opinions.